Performance analysis of AUV-carried RISs-aided multihop UWOC convergent with RF MRC systems over WGG oceanic turbulence - Zhou, Binna; Wang, Ping; Cao, Tian; Li, Ganggang; Li, Shuang; Yang, Pengfei (Vehicular Communications, 2024)
To establish reliable connection between Internet of Underwater Things (IoUT) devices and terrestrial data centers, this work first proposes a reconfigurable intelligent surface (RIS) aided multihop underwater wireless optical communication (UWOC) convergent with radio frequency (RF) uplink system. Specifically, the RIS carried by an autonomous underwater vehicle (AUV) is introduced into UWOC link to relax the line-of-sight (LOS) requirement and the maximal-ratio combining (MRC) receiver is adopted at the terrestrial data center to mitigate the RF link fading. It is assumed that the underwater thermocline channel is subject to the newly proposed Weibull-generalized gamma (WGG) turbulence distribution and the RF link composite fading follows Fisher-Snedecor F distribution. Additionally, the optical link misalignment is characterized by the zero-boresight pointing errors model. With the decode-and-forward (DF) relaying scheme, the analytical closed-form expressions of the outage probability (OP) and average bit error rate (ABER) of this system are mathematically achieved, and then the impacts of air bubbles, thermohaline gradient, the number of RIS elements, pointing errors, system structure, and the number of receive antennas are further investigated. Meanwhile, the analytical results are verified by Monte Carlo (MC) simulations. Results reveal that this hybrid system performance would degrade with the increased air bubble levels and thermohaline gradients. Notably, RIS can effectively alleviate the impact of underwater turbulence and this effect would be more pronounced as the number of RIS elements increases. This work will benefit the design and research of hybrid UWOC-RF system.